Corporate debt composition and business cycles - Jelena Živanović (Bank of Canada, 2019)
Based on empirical evidence, I propose a dynamic stochastic general equilibrium model with two financial sectors to analyze the role of corporate debt composition (bank versus bond financing) in the transmission of economic shocks. It is shown that in the presence of monetary and financial shocks, cyclical changes in corporate debt composition significantly attenuate the effects on investment and output. An additional result of the theoretical model is that a bank-dependent economy is more affected by financial shocks, which is in line with empirical results by Gambetti and Musso (2016), who report stronger real effects of loan supply shocks in Europe (with an excessive reliance on bank debt) than in the US.
Keywords: E32; E44; 330; Business fluctuation and cycles; Financial markets; Financial institutions; Recent economic and financial developments